Tangled roots : the emergence of Israeli culture - Barṭal, Yiśraʼel (Brown Judaic studies, 2020)
"In this new book Israel Bartal traces the history of modern Hebrew culture prior to the emergence of political Zionism. Bartal examines how traditional and modernist ideals and Western and non-European cultures merged in an unprecedented encounter between an ancient land (Israel) and a multigenerational people (the Jews). As this new Hebrew culture was taking shape, the memory of the recent European past played a highly influential role in shaping the image of the New Hebrew, that mythological hero who was meant to supplant the East European exilic Jew"--